2010
DOI: 10.4995/wrs.2005.526
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Detoxification of drinking water by ascorbic acid in growing rabbits.

Abstract: This work was carried out to study the capacity of ascorbic acid for detoxification of drinking water nitrate in growing New Zealand White rabbits. Forty growing female rabbits were assigned to five groups (8 rabbits/group). The control animals (group 1) drank tap water without nitrate addition, those of group 2 drank water with 729 mg/l nitrate, while rabbits of groups 3, 4 and 5 drank water with the same nitrate level plus 100, 200 and 400 mg/l ascorbic acid respectively for seven weeks. The nitrate caused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…The use of high levels of nitrate on rabbit performance was investigated by Gilman et al (1998); Bassuny et al (2004); Shehata (2005); and Djekoun-Bensoltane et al (2007). They showed that nitrate concentration at 600 to 700 ppm had a deleterious effect on rabbits' performance, but no attention was given to semen quality and litter traits.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of high levels of nitrate on rabbit performance was investigated by Gilman et al (1998); Bassuny et al (2004); Shehata (2005); and Djekoun-Bensoltane et al (2007). They showed that nitrate concentration at 600 to 700 ppm had a deleterious effect on rabbits' performance, but no attention was given to semen quality and litter traits.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that nitrate concentration at 600 to 700 ppm had a deleterious effect on rabbits' performance, but no attention was given to semen quality and litter traits. The adverse effect of nitrate was obvious with increasing nitrate intake in animals and humans (Shehata, 2005;DjekounBensoltane et al, 2007;Hord et al, 2009). Nitrate pollution -E-mail: attia0103753095@gmail.com could be increased because of agro-industry (Wahaab and Badawy, 2004;Burow et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations